The Effect of Cash Flow Components and Accounting Profit on Stock Returns Moderated by Company Size in Construction Companies on The Indonesian Stock Exchange in 2019-2023 - Tasya Anggeni; Estralita Trisnawati; Sriwati Sriwati (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to examine the effect of cash flow and accounting profit on stock returns in construction companies listed on the Indonesia Stock Exchange during the 2019–2023 period, with firm size as a moderating variable. Using a quantitative approach, the research utilized secondary data derived from annual financial reports, analyzed through panel data regression and Moderated Regression Analysis (MRA) using E-Views software and using SPSS software for the KMO test. The results showed that cash flow and accounting profit each have a positive and significant effect on stock returns, meaning that improvements in these financial indicators tend to increase investor returns. However, firm size was found to weaken the positive relationships between both cash flow and accounting profit with stock returns. In larger companies, the increase in cash flow or profit does not necessarily enhance investor trust, potentially due to more complex management and reporting structures. These findings highlight the need for companies to maintain efficient financial performance while managing their public image and transparency to maintain investor confidence. The study is limited to construction companies; future research is recommended to include broader sectors such as GCG or LQ-45 listed firms. The implication for company management is to pay strategic attention to cash flow, profitability, and company size to boost stock performance and investor appeal.